Keefektifan Teknik Latihan Asertif terhadap Komunikasi Interpersonal dan Konformitas Teman Sebaya Siswa - Akbar, Nur Yulianto; Wangid, Muhammad Nur; Prawitasari, Galuh (Jurnal Kajian Bimbingan dan Konseling, 2020)
Both interpersonal communication and conformity are prominent variables for adolescent’s social development. Adolescent who fails to establish a good interpersonal communication may turn to an aggressive individual, while the one who is too conformist will be more vulnerable to engage in juvenile delinquency. This study aims to investigate the effect of assertive training on interpersonal communication and peer conformity of junior high school students. 12 eighth graders of Junior High School Muhammadiyah 2 Mlati Yogyakarta were involved in the study. The study applied a Quasi Experimental approach with non-equivalent-groups pretest-posttest design. To gather research data, the study used Interpersonal Communication and Peer Conformity Scales. The result shows that assertive training is effective to increase interpersonal communication and to decrease the level of peer conformity. Based on the result, the next study needs to compare the effect of assertive training and other behavioral techniques on the two variables.